Integrasi Teknologi Digital dalam Pendidikan Islam: Kajian Konseptual Terhadap Transformasi Paradigma Pembelajaran di Era Revolusi Industri 5.0 - Gusmira, Yessy; Kurniati, Yeli; Sari, Desi Purnama; Oktavia , Wilni; Amra, Abhanda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the integration of digital technology in Islamic education. This research uses a literature study method (library research) that focuses on searching, collecting, analyzing, and synthesizing various relevant scientific sources. The classified literature is then analyzed in depth through a content analysis approach to explore key ideas, thought patterns, theoretical arguments, and the relevance of empirical findings. The analysis results show that the transformation of Islamic education in the era of the Industrial Revolution 5.0 is an inevitability that cannot be avoided. The development of digital technology such as artificial intelligence (AI), Learning Management Systems (LMS), and interactive learning media has shifted the learning paradigm from traditional models to more modern, collaborative, and technology-based systems. The integration of digital technology in Islamic education not only aims to enhance the effectiveness and efficiency of learning but also serves as an effort to strengthen the faith, morals, and character of students. Islamic value principles such as monotheism (tauhid), trustworthiness (amanah), justice, and public welfare serve as the ethical foundation that should guide every utilization of technology to ensure it brings benefits and avoids moral deviations. Thus, technology is not merely a tool, but also a medium for Islamic preaching and character building that is relevant to the challenges of the modern era.